Influence of Natural Gas Hydrate’s Property Weakening from Dissociation on Subsidence of Seabed Sediments: A Simulation Study - Shuzhi Ma; Hongbo Li; Hongbiao Jia (Advances in Civil Engineering)
The dissociation of natural gas hydrate in the seabed during hydrate production can lead to substantial weakening in soil mechanic properties, which in turn results in the deformation and even destruction of the seafloor sediments, thereby posing a potential threat to the safety of the undersea engineering infrastructures. A better understanding of the effect of soil mechanical weakening on seabed deformation will benefit the prediction and/or determination of geological conditions for safer hydrate production. In this work, a three-dimensional model of the submarine geological body was established and engineering properties of hydrate reservoir under different degrees of hydrate dissociation were determined. Such model and engineering parameters were applied for simulation calculation on examining the effect of hydrate dissociation degree on soil subsidence using FLAC3D software. The simulation results show that the subsidence of sediments is centrally distributed within the dissociation area and the subsidence of hydrate-bearing sediment’s top surface is much more severe than that of the overlying layer. Subsidence on the horizontal section above the hydrate reservoir presents an essentially symmetric dish-like subsidence trough, with the greatest subsidence in the centre and approximately constant subsidence beyond the trough range. The radius of the subsidence trough increases with the increase of the degree of dissociation, and the increasing extent in the early dissociation stage (lower dissociation degree) is greater than in the middle and the later stage (higher dissociation degree). As the degree of hydrate dissociation increases, subsidence of both the overlying layer and the HBS increases. Especially when the decomposition exceeds a certain threshold, the seafloor subsidence increases rapidly. The simulation results in this work are of guiding significance for deformation monitoring and infrastructure deformation prevention in practical hydrate production projects.